Encryption of Reversible Data Hiding for Better Visibility and High Security. (2016) - Achuthshankar, Aswathy; Achuthshankar, Aswin; Arjun, K.P.; Sreenarayanan, N.M.
Abstract: Every Organization uses data encryption for securing their communication. It provides data integrity, confidentiality and authentication. The primary goal of this paper is to combine the reversible data hiding and encryption to get maximum security. There are some areas like military, medical, forensic, bank, etc. which cannot compromise with any security issue. In the above areas both data and image are highly confidential, so no permanent distortion is acceptable. The paper proposes the algorithm reversible data hiding with a novel lightweight software oriented symmetric stream cipher namely A-S algorithm. The reversible data hiding algorithm used here produces maximum data capacity and contrast improved cover image. When applying the A-S encryption algorithm on the reversible data hiding process results a very good amount of security level. This new combined algorithm tested with two different datasets and the result shows a maximum data capacity and enhanced contrast of the cover image. The paper also measures another important metric of performance which results an extra ordinary result.